2012
DOI: 10.1016/j.freeradbiomed.2011.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibition activates transcription factor Nrf2 and protects against cerebral ischemic damage

Abstract: Interest in histone deacetylase (HDAC)-based therapeutics as a potential treatment for stroke has grown dramatically. The neuroprotection of HDAC inhibition may involve multiple mechanisms, including modulation of transcription factor acetylation independent of histones. The transcription factor Nrf2 has been shown to be protective in stroke as a key regulator of antioxidant-responsive genes. Here, we hypothesized that HDAC inhibition might provide neuroprotection against mouse cerebral ischemia by activating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
138
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(147 citation statements)
references
References 49 publications
6
138
1
Order By: Relevance
“…In pre-clinical studies, four main classes of HDAC are under investigation: the short-chain fatty acids, such as sodium butyrate, phenylbutyrate, and valproic acid, the hyroxamic acids, such as TSA and SAHA, the epoxyketones, such as trapoxin, and the benzamides (Abel and Zukin, 2008). SAHA and TSA promote neuronal survival in animal models of ischemia (Gibson and Murphy, 2010;Baltan et al, 2011b;Wang et al, 2012;Noh et al, 2012) and epilepsy (Huang et al, 2002;Kobow and Blumcke, 2011). Intriguingly, valproic acid, which is commonly prescribed as an anticonvulsant drug, was subsequently discovered to be an HDAC inhibitor (Gottlicher et al, 2001).…”
Section: Hdac Inhibitorsmentioning
confidence: 99%
“…In pre-clinical studies, four main classes of HDAC are under investigation: the short-chain fatty acids, such as sodium butyrate, phenylbutyrate, and valproic acid, the hyroxamic acids, such as TSA and SAHA, the epoxyketones, such as trapoxin, and the benzamides (Abel and Zukin, 2008). SAHA and TSA promote neuronal survival in animal models of ischemia (Gibson and Murphy, 2010;Baltan et al, 2011b;Wang et al, 2012;Noh et al, 2012) and epilepsy (Huang et al, 2002;Kobow and Blumcke, 2011). Intriguingly, valproic acid, which is commonly prescribed as an anticonvulsant drug, was subsequently discovered to be an HDAC inhibitor (Gottlicher et al, 2001).…”
Section: Hdac Inhibitorsmentioning
confidence: 99%
“…In vitro analysis demonstrated that the HDAC inhibitor activated Nrf2, in part, by reducing expression of the suppressor Keap1, promoting Keap1/Nrf2 dissociation, and enhancing Nrf2 nuclear translocation [19]. Consistent with these in vitro findings, the addition of TSA to Nrf2-deficient mice did not confer protection from ischemia [19].…”
Section: Transcriptional Effectsmentioning
confidence: 70%
“…Relevant studies since then have revealed that VPA attenuates stroke-induced blood-brain barrier disruption [18], trichostatin A (TSA) is effective as a stroke neuroprotectant [19], and hints at the specific contributions of HDACs 4 and 5 to stroke injury [20]. Human brain comprises gray matter and WM in equal volumes, which means that injury sustained after a stroke involves both.…”
Section: Hdac Inhibition Reduces Ischemic Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…3HB is an endogenous HDAC inhibitor (Shimazu et al., 2013), and the inhibition of HDAC leads to the activation of the Nrf2 pathway (Wang et al., 2012), promoting protection against neuronal damage. Acetylation levels of histone H3, K9, K14, and K27 in the IF and 3HB groups were similar to those in the AL group (Fig.…”
Section: Resultsmentioning
confidence: 99%